Transcriptomics reveal useful resources for examining fruit development and variation in fruit size in Coccinia grandis - Panda, Mitrabinda; Pradhan, Seema; Mukherjee, Pulok K. (Frontiers in Plant Science, 2024)
Introduction The Cucurbitaceae family comprises many agronomically important members, that bear nutritious fruits and vegetables of great economic importance. Coccinia grandis, commonly known as Ivy gourd, belongs to this family and is widely consumed as a vegetable. Members of this family are known to display an impressive range of variation in fruit morphology. Although there have been studies on flower development in Ivy gourd, fruit development remains unexplored in this crop. Methods In this study, comparative transcriptomics of two Ivy gourd cultivars namely “Arka Neelachal Kunkhi” (larger fruit size) and “Arka Neelachal Sabuja” (smaller fruit size) differing in their average fruit size was performed. A de novo transcriptome assembly for Ivy gourd was developed by collecting fruits at different stages of development (5, 10, 15, and 20 days after anthesis i.e. DAA) from these two varieties. The transcriptome was analyzed to identify differentially expressed genes, transcription factors, and molecular markers. Results The transcriptome of Ivy gourd consisted of 155205 unigenes having an average contig size of 1472bp. Unigenes were annotated on publicly available databases to categorize them into different biological functions. Out of these, 7635 unigenes were classified into 38 transcription factor (TF) families, of which Trihelix TFs were most abundant. A total of 11,165 unigenes were found to be differentially expressed in both the varieties and the in silico expression results were validated through real-time PCR. Also, 98768 simple sequence repeats (SSRs) were identified in the transcriptome of Ivy gourd. Discussion This study has identified a number of genes, including transcription factors, that could play a crucial role in the determination of fruit shape and size in Ivy gourd. The presence of polymorphic SSRs indicated a possibility for marker-assisted selection for crop breeding in Ivy gourd. The information obtained can help select candidate genes that may be implicated in regulating fruit development and size in other fruit crops.